Peningkatan Pemahaman Kebersihan Melalui Sosialisasi Pembersihan Saluran Drainase di Desa Janti, Waru - Mohamad Djaelani; Yayu Sriwahyuni; Taufik Hidayatulloh (Fakultas Teknik Universitas Palangka Raya, 2026)
Poor maintenance of drainage channels in residential areas remains one of the main causes of water stagnation and potential flooding, particularly in rural regions. This condition is generally influenced by the low level of public understanding regarding the importance of routine drainage maintenance. This community service program aimed to improve residents’ understanding and awareness of drainage cleanliness in Janti Village, Waru District. The activity was conducted on November 8–9, 2025, involving 20 participants representing neighborhood associations (RT and RW). The implementation method applied an educational-participatory approach through several stages, including preliminary observation, preparation of educational materials, pre-test implementation, socialization sessions, interactive discussions, simple drainage cleaning practices, post-test, and activity evaluation. The evaluation instruments consisted of pre-test and post-test questionnaires analyzed using descriptive quantitative methods to measure participants’ improvement in understanding. The results showed an increase in the average participant understanding score from 30% before the activity to 70% after the socialization program. These findings indicate that the applied socialization method was effective in improving public knowledge regarding drainage functions, maintenance techniques, and the importance of community participation in maintaining environmental cleanliness. Furthermore, the activity encouraged community awareness to carry out sustainable drainage maintenance through collective community work and environmental participation. Therefore, this program has the potential to become a community service model that can be implemented in other areas facing similar problems.